The Role of Arbitration in Resolving Industrial Relations Disputes in Indonesia: A Case Study of Employment - Manswab Mahsen Abdulrahman; Nikmah Dalimunthe; Aryanti Khairunnisa Br Tarigan; Ridho Rama Ardana Sinaga (Jurnal Sahabat ISNU SU, 2024)
In employment relationships, industrial relations conflicts are common and require efficient, fair, and effective resolution mechanisms. This study examines how arbitration institutions function in resolving industrial relations disputes and evaluates their advantages, disadvantages, and shortcomings within the Indonesian legal system. This study examines arbitration as an alternative dispute resolution method outside the Industrial Relations Court using a normative juridical approach based on laws, legal literature, and scientific studies. The results indicate that arbitration plays a significant role in encouraging conflict resolution through deliberation and agreement between disputing parties. Arbitration offers several advantages compared to litigation, such as faster dispute resolution, lower costs, confidentiality, procedural flexibility, and greater legal certainty through final and binding decisions. By encouraging agreed solutions, arbitration can also help maintain healthy relationships between employers and employees. However, the mechanism has disadvantages. These include limited opportunities for appeal, the possibility of arbitrator bias, ambiguity, and dependence on the arbitrator's ability and honesty. Despite these shortcomings, arbitration remains a useful means of resolving industrial relations conflicts when conducted with professionalism, impartiality, and good faith from all parties involved. Therefore, arbitration helps build a fair, stable, and productive industrial relations system.